Protecting the dignity of displaced Syrians - Mansour, K (Refugee Studies Centre, University of Oxford, 2018)
What does dignity mean to Syrian refugees and practitioners? And what can humanitarian organisations do – or abstain from doing – to help Syrians preserve and protect their dignity?